Correction: An Anti-β-Amyloid vaccine for treating cognitive deficits in a mouse model of down syndrome. - Pavel V Belichenko; Rime Madani; Lorianne Rey-Bellet; Maria Pihlgren; Ann Becker; Adeline Plassard; Stephanie Vuillermot; Valérie Giriens; Rachel L Nosheny; Alexander M Kleschevnikov; Janice S Valletta; Sara K S Bengtsson; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0152471.].